A review of the role of pre-treatment on the treatment of food waste using microbial fuel cells. Issue 1 (31st December 2022) - Zafar, Hirra; Peleato, Nicolas; Roberts, Deborah
ABSTRACT: Food waste is primarily managed by incineration or disposal in landfills. These current management methods can result in adverse environmental effects, are expensive, and do not necessarily take advantage of the remaining energy potential in food waste. Alternative treatment technologies such as microbial fuel cells (MFCs) are an attractive disposal method since overall organic concentrations can be reduced, and some of the chemical energy of the food waste can be transformed into electrical energy. MFC research has focused on the use of liquid waste due to advantages such as easy handling, low internal resistance, and efficiency of ion transfer in the liquid phase. While some researchers have shown the potential of using complex solid waste as a direct fuel in MFC, there remain significant challenges for optimizing complex solid food waste-fed MFCs. In particular, the biological degradation of the complex substrates in food waste is a slow process and requires additional pre-treatment (physical, thermal, chemical, or biological) to degrade complex biopolymers efficiently. As such, this article aims to review the impact and importance of various pre-treatment methods for optimizing performance of food waste fed MFCs. It is clear that direct use of solid waste in MFCs can be promising if several factors are optimized, including the pre-treatment used, substrate biodegradability, and operational cost. Although low power output is one of the main obstacles in the commercialization of MFC, MFC can still be considered a viable, self-sufficient treatment method to treat waste with minimum to zero emissions. GRAPHICAL ABSTRACT: UF0001